Haematoma of the buccal space in an edentulous patient – a case report. (20th May 2021) - Maciver, Rory; Ali, Sarah; Mackenzie, Fiona R.; Henderson, Neil
Abstract: Background: Oral swellings can be attributed to various causes, both odontogenic and non‐odontogenic in nature. This paper will discuss a buccal swelling caused by a haematoma. Case presentation: A 76‐year‐old edentulous male patient presented to a dental student outreach clinic with a three‐day history of a right‐sided facial swelling. No dental cause could be confirmed and so the patient was referred to the local secondary oral surgery department. The patient was examined, and an ultrasound of the swelling was arranged on the same day. The swelling was aspirated, and a haematoma was deemed the likely cause. After aspiration and a course of antibiotics, the swelling reduced rapidly. Blood tests were undertaken, and no underlying cause could be identified. Conclusions: Although uncommon, haematoma should be considered within differential diagnoses when dental pathology has been ruled out. A course of antibiotics is indicated where symptoms appear consistent with a systemic infection and timely referral to local dental hospital services is recommended. Blood tests should be requested to identify any undiagnosed coagulopathies or platelet abnormalities and liaison with local haematology services if resolution is not achieved would be appropriate.